The biological functions of ginsenoside and its applications in animal husbandry - Li, Yongqiang; Zhang, Guohui; Wang, Jingwei; Li, Jiahui; Liu, Yuhe; Pan, Shengsheng; Chang, Shihui; Gao, Yang (Frontiers in Veterinary Science, 2025)
Ginsenoside, as the pivotal bio-active constituents derived from ginseng, exhibit multifunctional biological properties including antioxidant, anti-inflammatory, immune regulation and stress-alleviating effects. Ginsenosides modulate immune responses, enhance metabolic regulation, and exert antioxidant effects through multiple pathways, improving animal health, meat quality and productivity. The purpose of this article is to provide solutions for the development of new feed additives under the premise of a complete ban on the use of antibiotics. Consequently, ginsenosides represent a premium botanical resource for feed additive applications in modern livestock and poultry production. This paper reviews the structural classification, source, biological function and application of ginsenoside in animals, in order to provide a reference for the rational use of ginsenoside in animal husbandry.